ANALISIS KEBERHASILAN PROGRAM PERLUASAN KEBUN KARET BIBIT UNGGUL CSR PT. ADARO INDONESIA - Hapijuddin Noor; Athaillan Mursyid; Abdul Haris; Hafizianor Hafizianor (Universitas Lambung Mangkurat, 2015)
The concept of CSR based on the values of participation, empowerment, and self-sufficiency (self reliance) in society is inseparable from the actual conditions and needs of the local community. One of the CSR programs undertaken by PT Adaro is people's rubber plantation development program by using seeds. Research done by conducting interviews of 36 people respondents specified in purposif to the community garden expansion program recipients rubber seeds PT Adaro Indonesia CSR in 2 (two) location of research, namely: Murung Pudak Subdistrict and Upau Subdistrict and the province of South Kalimantan. The results showed that success of the expansion of Rubber Garden Superior CSR PT Adaro Indonesia. seen from the aspect of the cultivation is high. The success of the expansion of Rubber Garden Superior CSR PT Adaro Indonesia. high as seen from socio-economic and cultural aspects of institutional is high. In order for the success that has been achieved can be maintained and upgraded again especially to aspect institutional, which needs to be done coaching, supervision and guidance on an ongoing basis to the existing institutional.